2014
DOI: 10.1186/1477-9560-12-5
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin and atrial fibrillation: from ideal to real the warfarin affaire

Abstract: Vitamin K Antagonists (VKAs) are widely used in clinical practice and nearly 1% of the entire population receives oral anticoagulation at least once in life. However, the rate of prescription of anticoagulation is low, compared to what it should be. No more than 50-60% of patients affected by atrial fibrillation (AF) receive anticoagulation. In the setting of AF, VKAs are safe and effective when properly managed, reducing stroke and systemic embolism by more than 60%. VKAs safety and effectiveness are closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 43 publications
(61 reference statements)
0
34
0
3
Order By: Relevance
“…Lower TTR values in real life patients rather than randomized controlled trial patients have been confirmed consistently throughout different countries [8,9]. Data on AF epidemiology and management in Turkey are quite limited and prospective mild-to long-term studies are lacking.…”
Section: Introductionmentioning
confidence: 98%
“…Lower TTR values in real life patients rather than randomized controlled trial patients have been confirmed consistently throughout different countries [8,9]. Data on AF epidemiology and management in Turkey are quite limited and prospective mild-to long-term studies are lacking.…”
Section: Introductionmentioning
confidence: 98%
“…It is estimated that 10-30% of AF are not diagnosed 32,35 and more than 40% of patients at high risk of stroke fail to receive guideline-recommended oral anticoagulant treatment 11,35 . 39 and increased risk of stroke 40,41 . All these gaps highlight unmet needs for stroke prevention in undiagnosed and undertreated AF, which will shed light on the strategies needed to eliminate disparities in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Квалитет антикоагулантне терапије пацијената са атријалном фибрилацијом у Дому здравља ''Нови Београд'' Општа медицина 2017;23 (3)(4):59-66…”
Section: ана M лончарunclassified
“…Израчунавањем CHA 2 DS 2 -VASc скора издвајамо па-цијенте са малим ризиком за мождани удар (мушкарци са скором 0 и жене са скором 0-1) код којих није индико-вана тромбопрофилакса, док су сви остали кандидати за примену оралне антикоагулантне терапије (АКТ)³. Адек-ватна орална антикоагулантна терапија смањује ризик од можданог удара за 65% и морталитет за 26% и далеко је ефикаснија од примене само аспирина (>50%) или двој-не антиагрегационе терапије (>30%) 4 . Прва терапијска линија у превенцији шлога код па-цијената са АФ јесу антагонисти витамина К (VKA).…”
Section: уводunclassified